Enhancing focus and self-control through traditional games in elementary school physical education - Novita Nur Synthiawati; Zakaria Wahyu Hidayat (Bima Loka: Journal of Physical Education, 2026)
This study aimed to examine the effectiveness of traditional games in improving focus and self-control among fifth-grade elementary school students. A quantitative approach with a one-group pretest-posttest design was employed. The participants consisted of 30 fifth-grade students from Grogol 1 State Elementary School, Diwek, Jombang. Data were collected using validated questionnaires measuring students' focus and self-control, which were administered before (pretest) and after (posttest) the implementation of traditional game-based activities. Data were analyzed using a paired-samples t-test to determine differences between pretest and posttest scores. The findings revealed that traditional games significantly improved students' focus and self-control (p < 0.001). For the focus variable, the paired-samples t-test showed a mean difference of −12.369 (t = −31.315, p < 0.001). Similarly, self-control demonstrated a mean difference of −28.696 (t = −78.220, p < 0.001). The negative mean differences indicate that posttest scores were significantly higher than pretest scores for both variables. These improvements can be attributed to the characteristics of traditional games, which require sustained attention, compliance with rules, cooperation, emotional regulation, and social interaction throughout gameplay. In conclusion, traditional games are an effective instructional strategy for enhancing elementary school students' focus and self-control. Integrating traditional games into physical education classes may support students' cognitive, social, and emotional development while creating a more engaging and enjoyable learning environment.